PLENARY POWERS OF SUBJECTS OF SPHERE OF SAFETY OF UKRAINE ARE FROM STOPPING OF MASS DISTURBANCES - Shmakov О. М.; Lavnіchenko О. V. (Honor and Law, 2019)
Approaches over are brought in relation to distribution of plenary powers between public authorities, forming of NGU and organs of police during stopping of mass disturbances depending on the stages and intensity of flowing of disturbances and determination of main performer by realization of measures on stopping of mass disturbances.